Making Waves: towards a harmonized approach for monitoring antimicrobial resistance in European surface waters - P. Krzeminski; C.U. Schwermer; M. Anglès d’Auriac; H. Bürgmann; H. Schmitt; J. Vierheilig; M. Gjeitnes; S.J. Moe; X. Bellanger; R. Carapeto García; P. Crespo Iniesta; C. Dagot; et al. (Water Research, 2026)

Bridging soil mapping units and digital soil mapping through probability-driven machine learning: an uncertainty-aware framework for soil class prediction in Antarctica - Rafael G. Siqueira; Cássio M. Moquedace; Márcio R. Francelino; Carlos Ernesto G.R. Schaefer; Roberto F.M. Michel; Daniela Schmitz; Flávia R. Ferrari; Caroline Delpupo; Eduardo O. Senra; Heitor P. Palma; Daniel N. Krum; Fábio S. de Oliveira; et al. (CATENA, 2026)

Challenges in estimating wolf population size using spatial count models and camera trap data - M.V. Boiani; P. Dupont; R. Bischof; O. Friard; F. Bisi; G. Bombieri; S. Calderola; S. Carolfi; C. Chioso; U. Fattori; P. Ferrari; S. Filacorda; et al. (Biological Conservation, 2026)

Incorporation of dose-rate effects into the BIANCA biophysical model and application for space radiation risk assessment - E.I. Canay; M. Carante; A. Casali; E. Bernardini; D. Dondi; Dhanalakshmi Vadivel; L. Cansolino; E. Delgrosso; C. Ferrari; M. Pullia; F. Bonforte; J. Riback; et al. (Life Sciences in Space Research, 2026)

An SDS-PAGE reverse-phase metaproteomics approach for polar desert and ornithogenic soils - Kristopher Abdullah; Arkadiusz Nawrocki; Daniel Wilkins; Ling Zhong; Dana Z. Tribbia; Martin R. Larsen; Belinda C. Ferrari (Applied Soil Ecology, 2026)

ISRM Suggested Methods for Triaxial Compression Testing of Shales and Mudstones - R. Ewy; E. Fjær; P. Delage; D. Dewhurst; J. Dudley; A. Ferrari; S. Giger; M. Soldal; J. Stenebråten; B. Crawford; S. Fontoura; L. Grande (Rock Mechanics and Rock Engineering, 2026)

Rivers under stress: geochemical changes along a rural–urban gradient during extreme hydrological events (Greve River, Italy) - M. Ferrari; R. Biagi; S. Venturi; F. Frezzi; F. Tassi (Environmental Geochemistry and Health, 2026)
Rivers are increasingly exposed to combined anthropogenic and climate-driven pressures, particularly along rural-to-urban gradients where land use, population density, and contaminant sources progressively intensify downstream. In parallel, prolonged droughts followed by intense rainfall events are becoming more frequent, potentially enhancing contaminant accumulation during dry periods and their rapid mobilization during subsequent first-flush events. However, the interactions between these hydrological extremes and spatial anthropogenic gradients in controlling river geochemistry remain insufficiently understood. This study investigates the spatial and seasonal evolution of river chemistry along the Greve River (Tuscany, Italy), a tributary of the Arno River, characterized by a marked rural-to-urban transition, during the exceptional 2022 European drought and subsequent heavy rainfall event. Six sampling campaigns were conducted between May and October 2022, combining high-resolution spatial monitoring with geochemical and isotopic tracers, including total dissolved solids (TDS), nutrients, and trace elements. The results reveal a progressive downstream enrichment in anthropogenic tracers (e.g., NO 3 − and K + , up to 9 mg/L and 6.6 mg/L, respectively) and pronounced evaporative isotope enrichment during the driest months (slope of the evaporation line ~ 4), indicating strong hydrological stress conditions. The first intense rainfall event triggered rapid remobilization of accumulated material and heterogeneous contaminant transport dynamics. Elevated nutrient concentrations (e.g., NH 4 + , up to 1.4 mg/L) in downstream sectors further reflect the combined influence of hydrological stress and urban inputs. These findings demonstrate how climate-driven hydrological extremes can amplify contaminant mobilization along urbanized river continuums. The integration of isotopic and geochemical tracers provides a transferable framework for assessing water-quality vulnerability in river basins increasingly exposed to hydroclimatic instability.

Association of meeting the 24-hour movement guidelines with heart rate variability in adults - Bruna T. C. Saraiva; William R. Tebar; Debora T. Furuta; Stefany C. B. Silva; Ewerton P. Antunes; Guilherme Sousa; Gerson Ferrari; Luiz Carlos M. Vanderlei; Diego Giulliano Destro Christofaro (European Journal of Applied Physiology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Correction: Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)

Novel antimicrobial and antiangiogenic properties from riparin-type benzamides: synthesis, biological evaluation, and docking analysis - Gabriela R. de Sousa; Janaracy L. da Costa Marinho; Pedro Thiago R. de Figueiredo; João Pedro A. Torres; Laísa V. Cordeiro; Luciana Scotti; Edeltrudes O. Lima; Bruna Braga Dantas; Fillipe de Oliveira Pereira; Jailton De Souza-Ferrari; José Maria Barbosa-Filho (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Measurement of the 244Cm neutron capture cross section at the n_TOF facility at CERN - V. Alcayne; A. Kimura; E. Mendoza; D. Cano-Ott; O. Aberle; F. Álvarez-Velarde; S. Amaducci; J. Andrzejewski; L. Audouin; V. Babiano-Suarez; M. Bacak; M. Barbagallo; et al. (Annals of Nuclear Energy, 2026)

Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)
Bees are essential for ecosystem functioning, pollinating many wild and crop plant species. Predicting which species are most vulnerable to global changes, and how their loss may impact ecosystems and human well-being, is critical. Comprehensive information on bee response and effect traits is fundamental to these assessments. However, the Raunkiærian shortfall—insufficient trait data—remains significant for bees, particularly in the Neotropics. Moreover, it remains uncertain whether conservation strategies based on functional diversity from temperate regions can be generalized to the Neotropics. To address this gap, we compiled a comprehensive and validated dataset on Brazilian bee traits, covering 24 traits related to sociality (100% of the species with some information), nesting (88%), body size (71%), and buzzing capacity (42%) on 2,066 Brazilian bee species. The trait data here presented is a crucial resource for evaluating bee species' pollination effectiveness and susceptibility to global change. Comparative analysis with regions with ample trait data—USA, Europe, and China—revealed notable differences. Brazilian bees exhibited a higher prevalence of aboveground nesting species, especially compared to Europe. The proportion of eusocial species was also greater than in Europe and the United States, and more similar to China. Differently from other regions, Brazilian eusocial bees were significantly smaller than their non-eusocial counterparts. These cross-regional comparisons highlight the importance of geographically tailored conservation strategies and underscore the need for extensive trait data to accurately predict regional vulnerabilities and ecological impacts in a rapidly changing world.

Correction: The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Fibroblast Activation Protein (FAP) as a possible therapeutic target in selected canine malignant tumours - S. Dell'Aere; D. Stefanello; E. Gariboldi; A. Ubiali; R. Ferrari; L. Auletta; M. Bocci; A. Galbiati; S. Cazzamalli; E. Gilardoni; V. Balbi; G. Bianchi; et al. (Journal of Comparative Pathology, 2025)

Platelet-derived growth factor receptor beta expression in primary and metastatic canine anal sac adenocarcinoma as a potential therapeutic target - A. Verdi; S. Dell'Aere; C. Zamboni; D. Stefanello; R. Ferrari; E. Gariboldi; L. Maniscalco; S. Iussich; C. Romanello; V. Grieco; C. Giudice; C. Recordati; et al. (Journal of Comparative Pathology, 2025)

Analysis of tight junction protein dynamics by immunohistochemistry in porcine intestinal epithelial cells (IPEC-J2) cells exposed to osmotic stress - B. Passeri; P. Borghetti; M. Andrani; M. Di Pentima; A. Luppi; E. De Angelis; V. Cavalli; L. Ferrari; R. Saleri (Journal of Comparative Pathology, 2025)

Splice me up, scotty: Extra domain-B fibronectin in canine tumours puts a spotlight on melanoma - S. Dell'Aere; D. Stefanello; E. Gariboldi; A. Ubiali; R. Ferrari; L. Auletta; M. Bocci; A. Galbiati; S. Cazzamalli; E. Gilardoni; A. Verdi; D. Neri; et al. (Journal of Comparative Pathology, 2025)

P18-57 Assessing cardiotoxicity of compounds in a 3D Heart-on-Chip platform by evaluating alterations in cardiac electrophysiology and contractility - C. Pernici; M. Mondini; M. Rasponi; E. Ferrari; R. Visone; P. Occhetta (Toxicology Letters, 2025)

The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Traditional and low-cost technical approaches for investigating greenhouse gases and particulate matter distribution along an urban-to-rural transect (Greve River Basin, Central Italy) - M. Ferrari; R. Biagi; S. Venturi; F. Frezzi; F. Tassi (Environmental Geochemistry and Health, 2025)
Human activities, largely tied to fossil fuels and intensive agriculture, emit massive amounts of climate-altering species and harmful pollutants into the atmosphere that affect soil, ecosystems, and water. Air quality monitoring is crucial to minimize harmful effects and protect human and environmental health. The Greve River basin (Tuscany, central Italy) represents an excellent example of an ecosystem affected by various anthropogenic air contaminants. The upstream areas are predominantly rural, while the downstream zones are characterized by urban and industrial development. Air pollutants throughout the basin were measured adopting two strategies: (i) fixed monitoring at five sites using multiparametric stations equipped with low-cost sensors for CO 2 , CH 4 , and PM 2.5 concentrations; (ii) measurements along a transect using a mobile monitoring station equipped with a Picarro G2201- i analyzer for the determination of CO 2 and CH 4 concentrations and 13 C/ 12 C values of the two gases. Results revealed relatively high CO 2 and CH 4 concentrations downstream, mainly due to vehicular traffic based on the isotopic signature. The temporal and spatial distribution of the contaminants mirrored the evolution of the Planetary Boundary Layer, with peak concentrations in the early morning due to stable atmospheric conditions, and contaminant dilution due to air turbulence during the daytime. Particulate (PM 2.5 ) distribution showed a trend similar to gaseous pollutants, being strongly dependent on wind speed and rainfall events. The high spatiotemporal resolution of data acquisition provided by the low-cost stations for air quality measurements represents an important advance for developing monitoring strategies, complementing the traditional instrumentation commonly used by agencies.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Spindle cell rhabdomyosarcoma in a cockatiel (Nymphicus hollandicus) - Tainah P. Dal Pont; Igor R. Santos; Vanessa C. Pereira; Flávia E. Ferrari; Victória R.Q. Schmidt; Marcele B. Bandinelli; Marcelo Meller Alievi; Saulo P. Pavarini (Journal of Comparative Pathology, 2025)

Retraction notice to “Toxicity of spike fragments SARS-CoV-2 S protein for zebrafish: A tool to study its hazardous for human health?” [Sci. Total Environ. 813 (2022) / 152345] - Bianca H. Ventura Fernandes; Natália Martins Feitosa; Ana Paula Barbosa; Camila Gasque Bomfim; Anali M.B. Garnique; Ivana F. Rosa; Maira S. Rodrigues; Lucas B. Doretto; Daniel F. Costa; Bruno Camargo-dos-Santos; Gabrielli A. Franco; João Favero Neto; et al. (Science of The Total Environment, 2024)

Assessing swelling-induced damage in shale samples during triaxial testing - E. Crisci; R. Ewy; A. Ferrari; S.B. Giger (Geomechanics for Energy and the Environment, 2024)

Shortcutting Photorespiration Protects Potato Photosynthesis and Tuber Yield Against Heatwave Stress - Katherine Meacham‐Hensold; Amanda P. Cavanagh; Peyton Sorensen; Paul F. South; Jessica Fowler; Ryan Boyd; Jooyeon Jeong; Steven Burgess; Samantha Stutz; Ryan N. Dilger; Moonsub Lee; Nicholas Ferrari; et al. (Global Change Biology, 2024)
Over two growing seasons, a chloroplast localized synthetic glycolate metabolic pathway expressed in potato, enhanced tuber biomass. We confirmed that this yield benefit did not come at the cost of tuber quality. In 2022, after two early season natural heatwaves, we observed enhanced daily carbon assimilation rates and increased photosynthetic capacity, with transformed plants having up to 23% higher V cmax and 13% higher J max during tuber bulking stages, indicating that transformed plants were better able to withstand growing season heatwaves than untransformed controls. The increases in photosynthetic capacity and potato tuber mass after early season heatwaves were greater than in seasons without heatwaves and present the AP3 pathway as a promising avenue for yield increases in the face of forecast increased intensity and duration of heatwave events as a result of global warming.

Cytogenetic analysis of meiotic behaviour and stability in a trigeneric hybrid (triticale x trigopiro) - M. Fradkin; E. J. Greizerstein; E. Grassi; V. Ferreira; M. R. Ferrari; L. Poggio (Protoplasma, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

The use of fishery and aquaculture by-products with Nannochloropsis sp. allows total dietary replacement of wild-caught fishmeal, fish oil and soy protein in European sea bass juveniles - A. Marchi; E. Benini; F. Dondi; M.G. Ferrari; D. Scicchitano; G. Palladino; M. Candela; R. Cerri; A. Di Biase; A.J. Vizcaíno; F.J. Alarcón-López; F.G. Acién; et al. (Aquaculture, 2024)

LGBTQ+ cancer: priority or lip service? A qualitative content analysis of LGBTQ+ considerations in U.S. state, jurisdiction, and tribal comprehensive cancer control plans - Austin R. Waters; Madeline H. Bono; Mayuko Ito Fukunaga; Manal Masud; Megan A. Mullins; Ryan Suk; Meghan C. O’Leary; Swann A. Adams; Renée M. Ferrari; Mary Wangen; Olufeyisayo O. Odebunmi; Sarah H. Nash; et al. (Cancer Causes & Control, 2024)

Thermal tolerance as a driver of reef fish community structure at the isolated tropical Mid-Atlantic Ridge Islands - Débora S. Ferrari; Lucas T. Nunes; Kirsty L. Jones; Carlos E.L. Ferreira; Sergio R. Floeter (Marine Environmental Research, 2024)

Insights from an extensive triaxial testing campaign on a shale for comparative site characterization of a deep geological repository - E. Crisci; S.B. Giger; L. Laloui; A. Ferrari; R. Ewy; R. Stankovic; J. Stenebråten; K. Halvorsen; M. Soldal (Geomechanics for Energy and the Environment, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Comparison of cytologicAL and histologicAL classification systems for the detection of nodal metastases of canine mast cell tumours - A. Renzi; M.G. Ferrari; R. Zaccone; L. Marconato; C. Agnoli; S. Zanardi; S. Sabattini (Journal of Comparative Pathology, 2024)

Effect of high-voltage electrical discharge (HVED) at high frequency on vacuum freeze-drying time and physicochemical properties of blueberries - R. Díaz-Álvarez; S. Carpentieri; G. Ferrari; G. Pataro; L. Segura-Ponce (Journal of Food Engineering, 2024)

A Global Systematic Literature Review of Ecosystem Services in Reef Environments - Vinicius J. Giglio; Anaide W. Aued; Cesar A. M. M. Cordeiro; Linda Eggertsen; Débora S. Ferrari; Leandra R. Gonçalves; Natalia Hanazaki; Osmar J. Luiz; André L. Luza; Thiago C. Mendes; Hudson T. Pinheiro; Bárbara Segal; et al. (Environmental Management, 2024)

Droplet size and hydraulic spray nozzles in peanut plant spray deposition - Gabriela G. P. Buosi; Arthur D. R. Neto; Paulo R. M. Lopes; Samuel Ferrari; Júlio C. Guerreiro; Pedro J. F. Filho; Ronaldo C. Lima; Vagner Nascimento; Marina Funichello; Carlos G. Raetano; Evandro P. Prado (Journal of Plant Diseases and Protection, 2024)

The Density of Callicebus coimbrai is Better Predicted by Vegetation Structure Variables than by Surrounding Landscape - Renato R. Hilário; Bárbara Moraes; João Pedro Souza-Alves; Stephen F. Ferrari (International Journal of Primatology, 2024)

Influence of Weather Conditions on Sleeping Patterns and Selection of Foliage Cover of Sleeping Trees in Black-and-Gold, Howler Monkeys (Alouatta caraya) in Northern Argentina - Melina V. Brividoro; Luciana I. Oklander; Verónica I. Cantarelli; Marina F. Ponzio; Héctor R. Ferrari; Martín M. Kowalewski (International Journal of Primatology, 2023)

Patient preferences for the design of a pharmacy-based colorectal cancer screening program - Alison T. Brenner; Austin R. Waters; Mary Wangen; Catherine Rohweder; Olufeyisayo Odebunmi; Macary Weck Marciniak; Renée M. Ferrari; Stephanie B. Wheeler; Parth D. Shah (Cancer Causes & Control, 2023)
Purpose To assess preferences for design of a pharmacy-based colorectal cancer (CRC) screening program (PharmFIT™) among screening-eligible adults in the United States (US) and explore the impact of rurality on pharmacy use patterns (e.g., pharmacy type, prescription pick-up preference, service quality rating). Methods We conducted a national online survey of non-institutionalized US adults through panels managed by Qualtrics, a survey research company. A total of 1,045 adults (response rate 62%) completed the survey between March and April 2021. Sampling quotas matched respondents to the 2010 US Census and oversampled rural residents. We assessed pharmacy use patterns by rurality and design preferences for learning about PharmFIT™; receiving a FIT kit from a pharmacy; and completing and returning the FIT kit. Results Pharmacy use patterns varied, with some notable differences across rurality. Rural respondents used local, independently owned pharmacies more than non-rural respondents (20.4%, 6.3%, p < 0.001) and rated pharmacy service quality higher than non-rural respondents. Non-rural respondents preferred digital communication to learn about PharmFIT™ (36% vs 47%; p < 0.001) as well as digital FIT counseling (41% vs 49%; p = 0.02) more frequently than rural participants. Preferences for receiving and returning FITs were associated with pharmacy use patterns: respondents who pick up prescriptions in-person preferred to get their FIT (OR 7.7; 5.3–11.2) and return it in-person at the pharmacy (OR 1.7; 1.1–2.4). Conclusion Pharmacies are highly accessible and could be useful for expanding access to CRC screening services. Local context and pharmacy use patterns should be considered in the design and implementation of PharmFIT™.

WRF data assimilation of weather stations and lightning data for a convective event in northern Italy - E. C. Maggioni; T. Manzoni; A. Perotto; F. Spada; A. Borroni; M. Giurato; M. Giudici; F. Ferrari; D. Zardi; R. Salerno (Bulletin of Atmospheric Science and Technology, 2023)

SARS-CoV-2 antibodies in inflammatory neurological conditions: a multicentre retrospective comparative study - Cecilia Zivelonghi; Alessandro Dinoto; Sarosh R. Irani; Andrew McKeon; Andrea Pilotto; Alessandro Padovani; Stefano Masciocchi; Eugenio Magni; Chiara R. Mancinelli; Ruggero Capra; Giorgia T. Maniscalco; Irene Volonghi; et al. (Immunologic Research, 2023)
It is well established that neurological and non-neurological autoimmune disorders can be triggered by viral infections. It remains unclear whether SARS-CoV-2 infection induces similar conditions and whether they show a distinctive phenotype. We retrospectively identified patients with acute inflammatory CNS conditions referred to our laboratory for antibody testing during the pandemic (March 1 to August 31, 2020). We screened SARS-COV-2 IgA/IgG in all sera by ELISA and confirmed the positivity with additional assays. Clinical and paraclinical data of SARS-COV-2-IgG seropositive patients were compared to those of seronegative cases matched for clinical phenotype, geographical zone, and timeframe. SARS-CoV-2-IgG positivity was detected in 16/339 (4%) sera, with paired CSF positivity in 3/16. 5 of these patients had atypical demyelinating disorders and 11 autoimmune encephalitis syndromes. 9/16 patients had a previous history of SARS-CoV-2 infection and 6 of them were symptomatic. In comparison with 32 consecutive seronegative controls, SARS-CoV-2-IgG-positive patients were older, frequently presented with encephalopathy, had lower rates of CSF pleocytosis and other neurological autoantibodies, and were less likely to receive immunotherapy. When SARS-CoV-2 seropositive versus seronegative cases with demyelinating disorders were compared no differences were seen. Whereas seropositive encephalitis patients less commonly showed increased CSF cells and protein, our data suggest that an antecedent symptomatic or asymptomatic SARS-CoV-2 infection can be detected in patients with autoimmune neurological conditions. These cases are rare, usually do not have specific neuroglial antibodies.

Opportunities and challenges in Asian bee research and conservation - Natapot Warrit; John Ascher; Parthib Basu; Vasuki Belavadi; Axel Brockmann; Damayanti Buchori; James B. Dorey; Alice Hughes; Smitha Krishnan; Hien T. Ngo; Paul Williams; Chao-Dong Zhu; et al. (Biological Conservation, 2023)

Metarhizium anisopliae E6 secretome reveals molecular players in host specificity and toxicity linked to cattle tick infection - Laura Rascovetzki Saciloto-de-Oliveira; Leonardo Broetto; Camila Innocente Alves; Rafael Lopes da Rosa; Yohana Porto Calegari Alves; Rodrigo Campos da Silva; Markus Berger; Alexandre José Macedo; Pedro Ferrari Dalberto; Cristiano Valim Bizarro; Jorge Almeida Guimarães; John R. Yates; et al. (Fungal Biology, 2023)

First report of oral cryptococcal osteomyelitis in a cat - Elisa Ferrari; Cássia R. de P. Secchin; Aline E. Santana (Brazilian Journal of Microbiology, 2023)

Survivin immunohistochemical expression in canine perivascular wall tumours: preliminary assessment - F. Godizzi; F. Armando; A. Cappelleri; P. Boracchi; D. Stefanello; R. Ferrari; L.E. Chiti; A. Corradi; G. Avallone; C. Pigoli; P. Roccabianca (Journal of Comparative Pathology, 2023)

Integrated ecosystem assessment around islands of the tropical South Mid-Atlantic Ridge - Amanda R. Rodrigues; Sergio R. Floeter; Vicente Gomes; Débora S. Ferrari; Vinicius J. Giglio; Fernanda C. Silva; Ana M. R. Liedke; Carlos E. L. Ferreira; Kerry Howell; Maria A. Gasalla (Frontiers in Marine Science, 2023)
The South Mid Atlantic Ridge comprises three main oceanic islands in the equatorial and tropical portions of the Atlantic Ocean. These islands are isolated from each other and equidistant from both the continental margins of South America and Africa, sharing common patterns but with different types of human use and pressures. Moreover, the areas beyond national jurisdiction between those islands are visited and exploited by distant fishing fleets and include large areas of shipping activity for commodities. Here, a pioneering integrated ecosystem assessment (IEA) process is constructed for the region among Saint Peter and Saint Paul’s Archipelago (Brazil), Saint Helena Island and Ascension Island (UK overseas territories). For that, we used a qualitative assessment of risks arising from anthropogenic activities, representing a novel contribution to the field. The Options for Delivering Ecosystem-Based Marine Management (ODEMM) approach was applied to trace sector–pressure–component pathways. A ‘linkage framework’ was outlined including pressures affecting each ecosystem component, and supported a process of knowledge attributions that scored the impact risks. All results were validated with regional stakeholders through workshops, including local and international management bodies, non-governmental organizations (NGOs) and scientists. The approach focused on a significant area among encompassing the open ocean, shallow and deep-sea biomes, analyzing the main sectors and pressures affecting the ecological components. Our results identified 14 sectors and 16 key pressures associated with 23 ecosystem components, totaling 780 impact chains. Fishing, shipping, wastewater, and tourism/recreation appeared as the top impacting sectors. Fishing and shipping were the most connected with ecosystem components links. Litter, species extraction, contaminants, and bycatch were the pressures that had the highest risk of impact values. Lastly, demersal and pelagic fish and pelagic and demersal elasmobranchs were the groups with the highest risk related to overall impacts, which were supported by local and regional evidence from long term monitoring programs and local studies. Our study demonstrated that these seemingly pristine islands and oceanic waters are already experiencing human impacts that should be addressed by local both conservation measures and international agreements. We also highlight the pressures that should be prioritized for better monitoring and policy, as well as those linkage components that have been less investigated.

Carotid artery stenting during endovascular thrombectomy for acute ischemic stroke with tandem occlusion: the Italian Registry of Endovascular Treatment in Acute Stroke - Fabrizio Sallustio; Giovanni Pracucci; Manuel Cappellari; Valentina Saia; Alfredo Paolo Mascolo; Federico Marrama; Roberto Gandini; Giacomo Koch; Marina Diomedi; Federica D’Agostino; Alessandro Rocco; Valerio Da Ros; et al. (Acta Neurologica Belgica, 2023)

TMS-evoked EEG potentials demonstrate altered cortical excitability in migraine with aura - Robert M. Helling; Matthijs J. L. Perenboom; Prisca R. Bauer; Johannes A. Carpay; Josemir W. Sander; Michel D. Ferrari; Gerhard H. Visser; Else A. Tolner (Brain Topography, 2023)
Migraine is associated with altered sensory processing, that may be evident as changes in cortical responsivity due to altered excitability, especially in migraine with aura. Cortical excitability can be directly assessed by combining transcranial magnetic stimulation with electroencephalography (TMS-EEG). We measured TMS evoked potential (TEP) amplitude and response consistency as these measures have been linked to cortical excitability but were not yet reported in migraine. We recorded 64-channel EEG during single-pulse TMS on the vertex interictally in 10 people with migraine with aura and 10 healthy controls matched for age, sex and resting motor threshold. On average 160 pulses around resting motor threshold were delivered through a circular coil in clockwise and counterclockwise direction. Trial-averaged TEP responses, frequency spectra and phase clustering (over the entire scalp as well as in frontal, central and occipital midline electrode clusters) were compared between groups, including comparison to sham-stimulation evoked responses. Migraine and control groups had a similar distribution of TEP waveforms over the scalp. In migraine with aura, TEP responses showed reduced amplitude around the frontal and occipital N100 peaks. For the migraine and control groups, responses over the scalp were affected by current direction for the primary motor cortex, somatosensory cortex and sensory association areas, but not for frontal, central or occipital midline clusters. This study provides evidence of altered TEP responses in-between attacks in migraine with aura. Decreased TEP responses around the N100 peak may be indicative of reduced cortical GABA-mediated inhibition and expand observations on enhanced cortical excitability from earlier migraine studies using more indirect measurements.

A trait‐based approach to marine island biogeography - Débora S. Ferrari; Sergio R. Floeter; Fabien Leprieur; Juan P. Quimbayo (Journal of Biogeography, 2023)
Aim The Island Biogeography Theory (IBT) and its multiple extensions explain species diversity patterns in insular systems. However, how these theories can predict the functional diversity patterns in island systems remains challenging. Here, we evaluated the predictions of the IBT, the General Dynamic Theory of Oceanic Island Biogeography (GDM) and the Glacial‐sensitive model of Island Biogeography (GSM) considering the functional diversity of reef fishes on islands. Location Tropical oceanic islands. Taxon Actinopterygii. Method We combined literature data and online repositories to gather occurrence data and traits of reef fish species for 72 tropical oceanic islands. We then calculated five functional diversity indices (functional richness ‘FRic’, functional evenness ‘FEve’, functional divergence ‘FDiv’, functional over‐redundancy ‘FOR’ and functional vulnerability ‘FVul’). We used generalized additive mixed models to explore relationships among species richness and functional indices. Furthermore, we built Bayesian models to evaluate relationships between the functional diversity indices and several island features (isolation from the nearest reef, past and present reef area, and geological age) and two metrics that reflect the potential influence of Quaternary climatic changes (isolation from Quaternary refugia) and historical contingency (isolation from biodiversity centres). Results We observed higher levels of FRic, FDiv and FOR on the Indo‐Pacific islands, whereas FEve and FVul showed higher values on the Atlantic and Eastern Pacific islands. We identified positive relationships between FRic, FDiv and FOR with species richness but negative relationships with FEve and FVul. We found that past and present reef areas best explained the variation in functional diversity among islands. Main Conclusions The functional diversity of reef fishes on oceanic islands showed a longitudinal gradient, which can be explained by differences in the evolutionary history among marine regions. Furthermore, past and present reef areas were found to be the best predictors of reef fish functional diversity on oceanic islands, extending the IBT, GDM and GSM for marine organisms within a trait‐based framework.

TimeFISH : Long‐term assessment of reef fish assemblages in a transition zone in the Southwestern Atlantic - Juan P. Quimbayo; Lucas T. Nunes; Fernanda C. Silva; Antônio B. Anderson; Diego R. Barneche; Angela M. Canterle; Isadora Cord; Andrea Dalben; Débora S. Ferrari; Luisa Fontoura; Thiago M. J. Fiuza; Ana M. R. Liedke; et al. (Ecology, 2023)
The TimeFISH database provides the first public time‐series dataset on reef fish assemblages in the southwestern Atlantic (SWA), comprising 15 years of data (2007–2022) based on standardized Underwater Visual Censuses (UVCs). The rocky reefs covered by our dataset are influenced by pronounced seasonal cycles of ocean temperatures with warm tropical waters from the Brazil Current in the summer (~27°C) and colder waters from the La Plata River Plume discharge and upwelling from the South Atlantic Central Water in the winter (~18°C). These oceanographic conditions characterize this area as the southernmost tropical–subtropical climatic transition zone in the Atlantic Ocean. As a result, reef fish assemblages are comprised of both tropical and subtropical species. All records included in TimeFISH were collected using UVCs, a nondestructive method that allows the estimation of fish species richness, abundance, and body size distributions. UVCs were performed through 40 m 2 belt transects by scuba diving in nine locations along the southern Brazilian coast (25–29°S). Four of these locations lie within the boundaries of the no‐entry Arvoredo Marine Biological Reserve, where fishing and recreational activities are forbidden, and the remaining locations are unprotected from these activities. During each belt transect, a diver swam at a constant depth above and parallel to the reef, identifying fish species, counting the number of individuals, and estimating the total body length (Lt in cm) of all detected individuals. All fish individuals in the water column (up to 2 m above the substratum) and at the bottom were targeted. In total, 202,965 individuals belonging to 163 reef fish species and 53 families were recorded across 1857 UVCs. All survey campaigns were funded by either public or mixed capital (private–public) sources, including seven grants from the Brazilian federal and Santa Catarina state governments. Part of the data has already been used in multiple MS.c. and Ph.D. theses and scientific articles. TimeFISH represents an important contribution for future studies aiming to examine temporal and spatial variations of reef fish assemblages in transition zones. No copyright restrictions apply to the use of this data set, other than citing this publication.

Functional consequences of allotypic polymorphisms in human immunoglobulin G subclasses - Andrew R. Crowley; Simone I. Richardson; Marina Tuyishime; Madeleine Jennewein; Meredith J. Bailey; Jiwon Lee; Galit Alter; Guido Ferrari; Lynn Morris; Margaret E. Ackerman (Immunogenetics, 2023)

Improving winter thermal comfort in Mediterranean buildings upgrading the envelope: An adaptive assessment based on a real survey - T. Blázquez; R. Suárez; S. Ferrari; J.J. Sendra (Energy and Buildings, 2023)

BAG2 prevents Tau hyperphosphorylation and increases p62/SQSTM1 in cell models of neurodegeneration - Raquel S. Lima; Daniel C. Carrettiero; Merari F. R. Ferrari (Molecular Biology Reports, 2022)

Spatial compositional turnover varies with trophic level and body size in marine assemblages of micro‐ and macroorganisms - Amanda K. Pettersen; Melinda A. Coleman; Guillaume Latombe; Sebastian Vadillo Gonzalez; Nathan L. R. Williams; Justin R. Seymour; Alexandra H. Campbell; Torsten Thomas; Renata Ferrari; Rick D. Stuart‐Smith; Graham J. Edgar; Peter D. Steinberg; et al. (Global Ecology and Biogeography, 2022)
Aim Spatial compositional turnover varies considerably among co‐occurring assemblages of organisms, presumably shaped by common processes related to species traits. We investigated patterns of spatial turnover in a diverse set of marine assemblages using zeta diversity, which extends traditional pairwise measures of turnover to capture the roles of both rare and common species in shaping assemblage turnover. We tested the generality of hypothesized patterns related to ecological traits and provide insights into mechanisms of biodiversity change. Location Temperate pelagic and benthic marine assemblages of micro‐ and macroorganisms along south‐eastern Australia (30–36° S latitude). Time period 2008–2021. Major taxa studied Bacteria, phytoplankton, zooplankton, fish, and macrobenthic groups. Methods Six marine datasets spanning bacteria to fishes were collated for measures of “species” occurrence, with a 1° latitude grain. For each assemblage, ecological traits of body size, habitat and trophic level were analysed for the form and rate of decline in zeta diversity and for the species retention rate. Results Species at higher trophic levels showed two to three times the rate of zeta diversity decline compared with lower trophic levels, indicating an increase in turnover from phytoplankton to carnivorous fishes. Body size showed the hypothesized unimodal relationship with rates of turnover for macroorganisms. Patterns of bacterial turnover contrasted with those found for macroorganisms, with the highest levels of turnover in pelagic habitats compared with benthic (kelp‐associated) habitats. The shape of retention rate curves showed the importance of both rare and common species in driving turnover; a finding that would not have been observable using pairwise (beta diversity) measures of turnover. Main conclusions Our results support theoretical predictions for phytoplankton and macroorganisms, showing an increase in turnover rate with trophic level, but these predictions did not hold for bacteria. Such deviations from theory need to be investigated further to identify underlying processes that govern microbial assemblage dynamics.

Effects of Magnetite Nanoparticles and Static Magnetic Field on Neural Differentiation of Pluripotent Stem Cells - Ana T. Semeano; Fabiano A. Tofoli; Juliana C. Corrêa-Velloso; Ana P. de Jesus Santos; Ágatha Oliveira-Giacomelli; Rafaela R. Cardoso; Mateus A. Pessoa; Edroaldo Lummertz da Rocha; Gustavo Ribeiro; Merari F. R. Ferrari; Lygia V. Pereira; Yang D. Teng; et al. (Stem Cell Reviews and Reports, 2022)

Genome-wide association study reveals white lupin candidate gene involved in anthracnose resistance - Joris A. Alkemade; Nelson Nazzicari; Monika M. Messmer; Paolo Annicchiarico; Barbara Ferrari; Ralf T. Voegele; Maria R. Finckh; Christine Arncken; Pierre Hohmann (Theoretical and Applied Genetics, 2022)
Key message GWAS identifies candidate gene controlling resistance to anthracnose disease in white lupin. Abstract White lupin ( Lupinus albus L.) is a promising grain legume to meet the growing demand for plant-based protein. Its cultivation, however, is severely threatened by anthracnose disease caused by the fungal pathogen Colletotrichum lupini . To dissect the genetic architecture for anthracnose resistance, genotyping by sequencing was performed on white lupin accessions collected from the center of domestication and traditional cultivation regions. GBS resulted in 4611 high-quality single-nucleotide polymorphisms (SNPs) for 181 accessions, which were combined with resistance data observed under controlled conditions to perform a genome-wide association study (GWAS). Obtained disease phenotypes were shown to highly correlate with overall three-year disease assessments under Swiss field conditions ( r > 0.8). GWAS results identified two significant SNPs associated with anthracnose resistance on gene Lalb_Chr05_g0216161 encoding a RING zinc-finger E3 ubiquitin ligase which is potentially involved in plant immunity. Population analysis showed a remarkably fast linkage disequilibrium decay, weak population structure and grouping of commercial varieties with landraces, corresponding to the slow domestication history and scarcity of modern breeding efforts in white lupin. Together with 15 highly resistant accessions identified in the resistance assay, our findings show promise for further crop improvement. This study provides the basis for marker-assisted selection, genomic prediction and studies aimed at understanding anthracnose resistance mechanisms in white lupin and contributes to improving breeding programs worldwide.

Editorial: Advances in 3D Habitat Mapping of Marine Ecosystem Ecology and Conservation - Renata Ferrari; Javier X. Leon; Andrew J. Davies; John H. R. Burns; Stuart A. Sandin; Will F. Figueira; Manuel Gonzalez-Rivero (Frontiers in Marine Science, 2022)

The Effects of Social Factors and Kinship on Co-sleeping of Black-and-Gold Howler Monkeys (Alouatta caraya) - Melina V. Brividoro; Luciana I. Oklander; Verónica I. Cantarelli; Marina F. Ponzio; Héctor R. Ferrari; Martin M. Kowalewski (International Journal of Primatology, 2021)

Forget the audience: tadpoles release similar disturbance cues regardless of kinship or familiarity - Kevin R. Bairos-Novak; Adam L. Crane; Gabrielle H. Achtymichuk; Jonathan Hsin; Ita A. E. Rivera-Hernández; Olena M. Simko; Theresa E. Wrynn; Douglas P. Chivers; Maud C. O. Ferrari (Behavioral Ecology and Sociobiology, 2020)

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Seismological analyses of the seismic microzonation of 138 municipalities damaged by the 2016–2017 seismic sequence in Central Italy - E. Priolo; F. Pacor; D. Spallarossa; G. Milana; G. Laurenzano; M. A. Romano; C. Felicetta; S. Hailemikael; F. Cara; G. Di Giulio; G. Ferretti; C. Barnaba; et al. (Bulletin of Earthquake Engineering, 2020)
This paper describes the seismological analyses performed within the framework of the seismic microzonation study for the reconstruction of 138 municipalities damaged by the 2016–2017 sequence in Central Italy. Many waveforms were recorded over approximately 15 years at approximately 180 instrumented sites equipped with permanent or temporary stations in an area that includes all the damaged localities. Site response was assessed using earthquake and noise recordings at the selected stations through different parameters, such as spectral amplification curves, fundamental resonance frequencies, site-specific response spectra, and average amplification factors. The present study was a collaboration of many different institutions under the coordination of the Italian Center for Seismic Microzonation and its applications . The results were homogenized and gathered into site-specific forms, which represent the main deliverable for the benefit of Italian Civil Protection. It is remarkable that the bulk of this study was performed in a very short period (approximately 2 months) to provide quantitative information for detailed microzonation and future reconstruction of the damaged municipalities.

Hesperidin methyl chalcone interacts with NFκB Ser276 and inhibits zymosan-induced joint pain and inflammation, and RAW 264.7 macrophage activation - Fernanda S. Rasquel-Oliveira; Marilia F. Manchope; Larissa Staurengo-Ferrari; Camila R. Ferraz; Telma Saraiva-Santos; Tiago H. Zaninelli; Victor Fattori; Nayara A. Artero; Stephanie Badaro-Garcia; Andressa de Freitas; Rubia Casagrande; Waldiceu A. Verri (Inflammopharmacology, 2020)

Reduction of hippocampal IL-6 levels in LPS-injected rats following acute exendin-4 treatment - Luiza P. Géa; Eduarda D. da Rosa; Bruna S. Panizzutti; Érica Z. de Aguiar; Larissa F. de Oliveira; Pamela Ferrari; Angelo Piato; Rosane Gomez; Rafael Colombo; Adriane R. Rosa (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Lime and gypsum combination improves crop and forage yields and estimated meat production and revenue in a variable charge tropical soil - Carlos A. C. Crusciol; Rubia R. Marques; Antonio C. A. Carmeis Filho; Rogério P. Soratto; Claudio H. M. Costa; Jayme Ferrari Neto; Gustavo S. A. Castro; Cristiano M. Pariz; André M. Castilhos; Alan J. Franzluebbers (Nutrient Cycling in Agroecosystems, 2019)

Does Sugarcane Straw Removal Change the Abundance of Soil Microbes? - Maristela C. Morais; Beatriz M. Ferrari; Clovis D. Borges; Maurício R. Cherubin; Siu Mui Tsai; Carlos C. Cerri; Carlos E. P. Cerri; Brigitte J. Feigl (BioEnergy Research, 2019)

Anointing with commercial insect repellent by free-ranging Cebus capucinus in Manuel Antonio National Park, Quepos, Costa Rica - Edilton R. Santos; Stephen F. Ferrari; Raone Beltrão-Mendes; Gustavo A. Gutiérrez-Espeleta (Primates, 2019)

Terrestrial Behavior in Titi Monkeys (Callicebus, Cheracebus, and Plecturocebus): Potential Correlates, Patterns, and Differences between Genera - João Pedro Souza-Alves; Italo Mourthe; Renato R. Hilário; Júlio César Bicca-Marques; Jennifer Rehg; Carla C. Gestich; Adriana C. Acero-Murcia; Patrice Adret; Rolando Aquino; Mélissa Berthet; Mark Bowler; Armando M. Calouro; et al. (International Journal of Primatology, 2019)

Survival, behaviour, and morphology of larval wood frogs, Lithobates sylvaticus, under threat from an exotic crayfish predator, Orconectes virilis - Adam L. Crane; Kevin R. Bairos-Novak; Dale M. Jefferson; Douglas P. Chivers; Maud C. O. Ferrari (Aquatic Ecology, 2019)

Stereotactic radiation therapy in oligometastatic colorectal cancer: outcome of 102 patients and 150 lesions - V. Dell’Acqua; A. Surgo; F. Kraja; J. Kobiela; Maria Alessia Zerella; P. Spychalski; S. Gandini; C. M. Francia; D. Ciardo; C. Fodor; A. M. Ferrari; G. Piperno; et al. (Clinical & Experimental Metastasis, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Diallelic Analysis of Endogamic Maize Lines with Emphasis on Agronomic Traits of Tassel in Different Environments - D. Barreta; M. Nardino; V. A. Konflanz; A. J. de Pelegrin; M. Ferrari; V. J. Szareski; I. R. Carvalho; V. Q. de Souza; A. C. de Oliveira; L. C. da Maia (Journal of Crop Science and Biotechnology, 2019)

The Role of Stakeholders in Creating Societal Value From Coastal and Ocean Observations - Bev Mackenzie; Louis Celliers; Luiz Paulo de Freitas Assad; Johanna J. Heymans; Nicholas Rome; Julie Thomas; Clarissa Anderson; James Behrens; Mark Calverley; Kruti Desai; Paul M. DiGiacomo; Samy Djavidnia; et al. (Frontiers in Marine Science, 2019)

A combined stochastic analysis of mean daily temperature and diurnal temperature range - B. Sirangelo; T. Caloiero; R. Coscarelli; E. Ferrari (Theoretical and Applied Climatology, 2019)

Mild Exercise Differently Affects Proteostasis and Oxidative Stress on Motor Areas During Neurodegeneration: A Comparative Study of Three Treadmill Running Protocols - Karla P. Melo; Carolliny M. Silva; Michael F. Almeida; Rodrigo S. Chaves; Tania Marcourakis; Sandra M. Cardoso; Marilene Demasi; Luis E. S. Netto; Merari F. R. Ferrari (Neurotoxicity Research, 2019)

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Application of the Innovative Trend Analysis Method for the Trend Analysis of Rainfall Anomalies in Southern Italy - T. Caloiero; R. Coscarelli; E. Ferrari (Water Resources Management, 2018)

Marine infrastructure supports abundant, diverse fish assemblages at the expense of beta diversity - A. G. Porter; R. L. Ferrari; B. P. Kelaher; S. D. A. Smith; R. A. Coleman; M. Byrne; W. Figueira (Marine Biology, 2018)

Development of Transgenic Sugarcane Resistant to Sugarcane Borer - Plinio T. Cristofoletti; Edson L. Kemper; Adriana N. Capella; Sandra R. Carmago; Juliana L. Cazoto; Fernanda Ferrari; Tederson L. Galvan; Luciane Gauer; Gustavo A. Monge; Marcelo A. Nishikawa; Nicolas Z. Santos; Altair A. Semeao; et al. (Tropical Plant Biology, 2018)

Endoscopy, histology and electron microscopy analysis of foetal membranes in pregnant South American plains vizcacha reveal unusual excrescences on the yolk sac - Mariela Giacchino; Pablo I. F. Inserra; Fernando D. Lange; María C. Gariboldi; Sergio R. Ferraris; Alfredo D. Vitullo (Journal of Molecular Histology, 2018)

Environmental control of malting barley response to nitrogen in the Pampas, Argentina - P. Prystupa; G. Ferraris; L. Ventimiglia; T. Loewy; L. Couretot; R. Bergh; F. Gómez; F. H. Gutierrez Boem (International Journal of Plant Production, 2018)

Nucleolar activity in Triticum x Thinopyrum hybrids with different ploidy level - M. Fradkin; E. J. Greizerstein; M. R. Ferrari; L. Poggio (Plant Biosystems, 2017)

Temporal Analysis of Rainfall Categories in Southern Italy (Calabria Region) - T. Caloiero; R. Coscarelli; E. Ferrari; B. Sirangelo (Environmental Processes, 2017)

A stochastic model for the analysis of maximum daily temperature - B. Sirangelo; T. Caloiero; R. Coscarelli; E. Ferrari (Theoretical and Applied Climatology, 2017)

Quercetin inhibits gout arthritis in mice: induction of an opioid-dependent regulation of inflammasome - Kenji W. Ruiz-Miyazawa; Larissa Staurengo-Ferrari; Sandra S. Mizokami; Talita P. Domiciano; Fabiana T. M. C. Vicentini; Doumit Camilios-Neto; Wander R. Pavanelli; Phileno Pinge-Filho; Flávio A. Amaral; Mauro M. Teixeira; Rubia Casagrande; Waldiceu A. Verri (Inflammopharmacology, 2017)

The Neurobiology of Depression: an Integrated Overview from Biological Theories to Clinical Evidence - F. Ferrari; R. F. Villa (Molecular Neurobiology, 2017)

Trend analysis of monthly mean values and extreme indices of daily temperature in a region of southern Italy - T. Caloiero; R. Coscarelli; E. Ferrari; B. Sirangelo (International Journal of Climatology, 2017)
The analyses of temperature extremes can be very useful because they are highly representative of the climatic tendency of an area. In this study, 19 temperature series registered in southern Italy have been analysed for detecting trends through the Mann–Kendall non‐parametric test. The tendencies have been detected since 1951 for the maximum and minimum monthly temperatures and for several indices of daily extremes. As a result, the minimum and maximum monthly temperatures mainly denote a positive trend for spring and summer months and a marked negative one in September. Moreover, the trend analysis on the extreme temperature indices shows opposite behaviours: a clear positive tendency in the frequency and intensity of the highest values and some negative trends for the lowest ones.

Perovskite-type titanate zirconate as photocatalyst for textile wastewater treatment - A. M. Ferrari-Lima; A. C. Ueda; E. A. Bergamo; R. G. Marques; E. A. V. Ferri; C. S. Pinto; C. A. A. Pereira; P. H. Yassue-Cordeiro; R. P. Souza (Environmental Science and Pollution Research, 2017)

A primate at risk in Northeast Brazil: local extinctions of Coimbra Filho’s titi (Callicebus coimbrai) - Renato R. Hilário; Leandro Jerusalinsky; Sidnei Santos; Raone Beltrão-Mendes; Stephen F. Ferrari (Primates, 2017)

Impairment of mitochondria dynamics by human A53T α-synuclein and rescue by NAP (davunetide) in a cell model for Parkinson’s disease - T. Q. Melo; K. C. van Zomeren; M. F. R. Ferrari; H. W. G. M. Boddeke; J. C. V. M. Copray (Experimental Brain Research, 2017)

Stochastic analysis of long dry spells in Calabria (Southern Italy) - B. Sirangelo; T. Caloiero; R. Coscarelli; E. Ferrari (Theoretical and Applied Climatology, 2017)

Cystic fibrosis in Afro-Brazilians: XK haplotypes analysis supports the European origin of p.F508del mutation - D. A. S. de Souza; F. R. Faucz; R. B. de Alexandre; M. A. Santana; E. L. S. de Souza; F. J. C. Reis; L. Pereira-Ferrari; V. S. Sotomaior; L. Culpi; J. A. Phillips; S. Raskin (Genetica, 2017)

Polymorphisms of dopamine receptor genes and risk of visual hallucinations in Parkinson’s patients - M Ferrari; C Comi; F Marino; L Magistrelli; F De Marchi; R Cantello; G Riboldazzi; G Bono; M Cosentino (European Journal of Clinical Pharmacology, 2016)

Gene co-expression analysis identifies brain regions and cell types involved in migraine pathophysiology: a GWAS-based study using the Allen Human Brain Atlas - Else Eising; Sjoerd M. H. Huisman; Ahmed Mahfouz; Lisanne S. Vijfhuizen; Verneri Anttila; Bendik S. Winsvold; Tobias Kurth; M. Arfan Ikram; Tobias Freilinger; Jaakko Kaprio; Dorret I. Boomsma; Cornelia M. van Duijn; et al. (Human Genetics, 2016)

An Overview of an Acidic Uranium Mine Pit Lake (Caldas, Brazil): Composition of the Zooplankton Community and Limnochemical Aspects - Carla R. Ferrari; Heliana de Azevedo; Maria José S. Wisniewski; Suzelei Rodgher; Cláudio Vitor Roque; Marcos Roberto L. Nascimento (Mine Water and the Environment, 2015)

A stochastic model for the analysis of the temporal change of dry spells - B. Sirangelo; T. Caloiero; R. Coscarelli; E. Ferrari (Stochastic Environmental Research and Risk Assessment, 2015)

Seismicity of Northwestern Italy during the last 30 years - D. Scafidi; S. Barani; R. De Ferrari; G. Ferretti; M. Pasta; M. Pavan; D. Spallarossa; C. Turino (Journal of Seismology, 2015)

The ruthenium nitric oxide donor, [Ru(HEDTA)NO], inhibits acute nociception in mice by modulating oxidative stress, cytokine production and activating the cGMP/PKG/ATP-sensitive potassium channel signaling pathway - Larissa Staurengo-Ferrari; Sandra S. Mizokami; Victor Fattori; Jean J. Silva; Patrícia G. Zanichelli; Sandra R. Georgetti; Marcela M. Baracat; Luiz G. da França; Wander R. Pavanelli; Rubia Casagrande; Waldiceu A. Verri (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Latitudinal pattern in plant composition along the Peruvian and Chilean fog oases - R. Manrique; C. Ricotta; C. Ferrari; G. Pezzi (Plant Biosystems, 2014)

Social learning of predators by coral reef fish: does observer number influence acquisition of information? - R. P. Manassa; M. I. McCormick; D. L. Dixson; M. C. O. Ferrari; D. P. Chivers (Behavioral Ecology and Sociobiology, 2014)

Bronchial microbiome of severe COPD patients colonised by Pseudomonas aeruginosa - L. Millares; R. Ferrari; M. Gallego; M. Garcia-Nuñez; V. Pérez-Brocal; M. Espasa; X. Pomares; C. Monton; A. Moya; E. Monsó (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Modeling the spread of invasive species using dynamic network models - Joseph R. Ferrari; Evan L. Preisser; Matthew C. Fitzpatrick (Biological Invasions, 2014)

Influence of the North Atlantic Oscillation on winter rainfall in Calabria (southern Italy) - E. Ferrari; T. Caloiero; R. Coscarelli (Theoretical and Applied Climatology, 2013)

Quantitative panbiogeography: was the congruence problem solved? - Augusto Ferrari; Kim R. Barão; Felipe L. Simões (Systematics and Biodiversity, 2013)

Investigating the feasibility of using DNA from sloughed skin for individual identification and kinship analysis in humpback whales ( Megaptera novaeangliae ) - S. P. Pierszalowski; M. Ferrari; D. Glockner‐Ferrari; S. Mizroch; P. J. Clapham; B. R. Dickerson (Marine Mammal Science, 2013)

Fruits of Mimosa foliolosa (Fabales: Fabaceae) as Sleeping Shelter for Megachile (Pseudocentron) botucatuna (Hymenoptera: Megachilidae) - G W Fernandes; R R Ferrari (Neotropical Entomology, 2012)

The effectiveness of different meso-scale rugosity metrics for predicting intra-habitat variation in coral-reef fish assemblages - Alastair R. Harborne; Peter J. Mumby; Renata Ferrari (Environmental Biology of Fishes, 2012)

Do fathead minnows, Pimephales promelas Rafinesque, alter their club cell investment in responses to variable risk of infection from Saprolegnia ? - R J Pollock; M S Pollock; M C O Ferrari; S G W Kaminskyj; D P Chivers (Journal of Fish Diseases, 2012)
Fish in the Superorder Ostariophysi possess large epidermal club cells that release chemical cues warning nearby conspecifics of danger. Despite the long‐held assumption that such club cells evolved under the selective force of predation, recent studies demonstrated that predation has no effect on club cell investment. Rather, club cells have an immune function and cell production may be stimulated by skin‐penetrating pathogens and parasites. The current work investigates whether fathead minnows, Pimephales promelas , alter their club cell characteristics based on variation in infection risk. In a 2 × 3 design, we exposed minnows to infective cysts of two oomycete species ( Saprolegnia ferax and S. parasitica ) at three different concentrations (2, 20 or 200 cysts L −1 ). Club cell characteristics (number and size) were quantified 12 days after exposure. Saprolegnia parasitica is thought to be more pathogenic than S. ferax , hence we predicted greater club cell investment and a larger turnover rate of cells by minnows exposed to S. parasitica than S. ferax. We also predicted that minnows exposed to higher numbers of cysts should invest more in club cells and have a higher turnover rate of cells. We found no difference in club cell density or size between fish exposed to the two Saprolegnia species; however, fish exposed to high concentrations of pathogens had smaller club cells than those exposed to low concentrations, indicating a higher rate of turnover of cells in the epidermis.

Assessing and promoting old-growthness of forest stands: Lessons from research in Italy - A. Barbati; R. Salvati; B. Ferrari; D. Di Santo; A. Quatrini; L. Portoghesi; D. Travaglini; F. Iovino; S. Nocentini (Plant Biosystems, 2012)

Connectivity of Caribbean coral populations: complementary insights from empirical and modelled gene flow - NICOLA L. FOSTER; CLAIRE B. PARIS; JOHNATHAN T. KOOL; ILIANA B. BAUMS; JAMIE R. STEVENS; JUAN A. SANCHEZ; CAROLINA BASTIDAS; CLAUDIA AGUDELO; PHILLIPPE BUSH; OWEN DAY; RENATA FERRARI; PATRICIA GONZALEZ; et al. (Molecular Ecology, 2012)
Understanding patterns of connectivity among populations of marine organisms is essential for the development of realistic, spatially explicit models of population dynamics. Two approaches, empirical genetic patterns and oceanographic dispersal modelling, have been used to estimate levels of evolutionary connectivity among marine populations but rarely have their potentially complementary insights been combined. Here, a spatially realistic Lagrangian model of larval dispersal and a theoretical genetic model are integrated with the most extensive study of gene flow in a Caribbean marine organism. The 871 genets collected from 26 sites spread over the wider Caribbean subsampled 45.8% of the 1900 potential unique genets in the model. At a coarse scale, significant consensus between modelled estimates of genetic structure and empirical genetic data for populations of the reef‐building coral Montastraea annularis is observed. However, modelled and empirical data differ in their estimates of connectivity among northern Mesoamerican reefs indicating that processes other than dispersal may dominate here. Further, the geographic location and porosity of the previously described east–west barrier to gene flow in the Caribbean is refined. A multi‐prong approach, integrating genetic data and spatially realistic models of larval dispersal and genetic projection, provides complementary insights into the processes underpinning population connectivity in marine invertebrates on evolutionary timescales.

Use of water sources by buffy-headed marmosets (Callithrix flaviceps) at two sites in the Brazilian Atlantic Forest - Stephen F. Ferrari; Renato R. Hilário (Primates, 2012)

Influence of air pressure, humidity, solar radiation, temperature, and wind speed on ambulatory visits due to chronic obstructive pulmonary disease in Bavaria, Germany - Uta Ferrari; Teresa Exner; Eva R Wanka; Christoph Bergemann; Julian Meyer-Arnek; Beate Hildenbrand; Amanda Tufman; Christian Heumann; Rudolf M Huber; Michael Bittner; Rainald Fischer (International Journal of Biometeorology, 2012)

A molecular analysis of the evolutionary relationships in the Callitrichinae, with emphasis on the position of the dwarf marmoset - Horacio Schneider; Jose Antonio R. Bernardi; Divino B. Da Cunha; Claudia H. Tagliaro; Marcelo Vallinoto; Steve F. Ferrari; Iracilda Sampaio (Zoologica Scripta, 2012)
Schneider, H., Bernardi, J. A. R., da Cunha, D. B., Tagliaro, C. H., Vallinoto, M., Ferrari, S. F. & Sampaio, I. (2011). A molecular analysis of the evolutionary relationships in the Callitrichinae, with emphasis on the position of the dwarf marmoset. — Zoologica Scripta , 41 , 1–10. The phylogenetic relationships among the Neotropical primates of the subfamily Callitrichinae (marmosets and tamarins) are controversial, especially with regard to the proposal of a new marmoset genus, Callibella , based on the analysis of sequences of a single mitochondrial gene. In this study, we combine the fast‐evolving mitochondrial Control Region with four nuclear regions containing Alu elements in an attempt to provide a more conclusive assessment of the phylogenetic relationships among the marmosets ( Callithrix , Cebuella and Mico ), with special attention to the validity of Callibella . A large, representative sample of specimens was obtained, which include all the recognized genera and principal morphological and geographic groupings. The results of the analysis indicate unequivocally the existence of three independent lineages, corresponding to the Atlantic Forest ( Callithrix ), Amazonian ( Mico ) and pygmy marmoset ( Cebuella ) groups. The evidence also confirms the monophyletic relationship of the dwarf marmoset ( Callibella ) with the Amazonian marmosets ( Mico ), which indicates conclusively that this taxon is a member of the genus Mico , upholding the original description of the species as Mico humilis .

Shutdown of turbulent convection as a new criterion for the onset of spring phytoplankton blooms - John R. Taylor; Raffaele Ferrari (Limnology and Oceanography, 2011)
The onset of phytoplankton blooms in late winter, early spring has been traditionally associated with the shoaling of the mixed layer above a critical depth. Here we show that the onset of a bloom can also be triggered by a reduction in air–sea fluxes at the end of winter. When net cooling subsides at the end of winter, turbulent mixing becomes weak, thereby increasing the residence time of phytoplankton cells in the euphotic layer and allowing a bloom to develop. The necessary change in the air–sea flux generally precedes mixed‐layer shoaling, and may provide a better indicator for the onset of the spring bloom than the mixed‐layer depth alone. Our hypothesis is supported by numerical simulations and remote sensing data.

Plasticity of Opioid Receptors in the Female Periaqueductal Gray: Multiparity-Induced Increase in the Activity of Genes Encoding for Mu and Kappa Receptors and a Post-Translational Decrease in Delta Receptor Expression - Elizabeth Teodorov; Maria M. Bernardi; Merari F. R. Ferrari; Debora R. Fior-Chadi; Luciano F. Felicio (Journal of Molecular Neuroscience, 2011)

Why Feed on Fungi? The Nutritional Content of Sporocarps Consumed by Buffy-Headed Marmosets, Callithrix flaviceps (Primates: Callitrichidae), in Southeastern Brazil - Renato R. Hilário; Stephen Francis Ferrari (Journal of Chemical Ecology, 2011)

Long‐term survival of humpback whales radio‐tagged in Alaska from 1976 through 1978 - Sally A. Mizroch; Michael F. Tillman; Susan Jurasz; Janice M. Straley; Olga Von Ziegesar; Louis M. Herman; Adam A. Pack; Scott Baker; Jim Darling; Debbie Glockner‐Ferrari; Mark Ferrari; Dan R. Salden; et al. (Marine Mammal Science, 2011)
Invasive tags designed to provide information on animal movements through radio or satellite monitoring have tremendous potential for the study of whales and other cetaceans. However, to date there have been no published studies on the survival of tagged animals over periods of years or decades. Researchers from the National Marine Mammal Laboratory and the Woods Hole Oceanographic Institution tracked five humpback whales with implanted radio tags in southeastern Alaska in August 1976 and July 1977, and tracked two humpback whales in Prince William Sound, Alaska, in June 1978. All seven of these individually identified humpback whales were resighted at least 20 yr after first being tagged, and five of the seven have been observed for more than 30 yr; some of them are among the most resighted humpback whales in the North Pacific. Photos of tagging sites taken during and subsequent to tagging operations show persistent but superficial scarring and no indication of infection. These pioneering field studies demonstrated both long‐term survival of the whales and the short‐term effects of deploying radio tags, which at the time were larger and more invasive than those typically used today.

Design and preparation of market baskets of European Union commercial baby foods for the assessment of infant exposure to food chemicals and to their effects - R. Piccinelli; M. Pandelova; C. Le Donne; M. Ferrari; K.-W. Schramm; C. Leclercq (Food Additives & Contaminants: Part A, 2010)

Chronic variable stress impairs energy metabolism in prefrontal cortex and hippocampus of rats: prevention by chronic antioxidant treatment - Bárbara Tagliari; Cristie G. Noschang; Andréia G. K. Ferreira; Otávio A. Ferrari; Luciane R. Feksa; Clovis M. D. Wannmacher; Carla Dalmaz; Angela T. S. Wyse (Metabolic Brain Disease, 2010)

Copper (II) adsorption studies using models of synthetic humic acids - Marcilene Ferrari Barriquello; N. Consolin-Filho; E. R. Carvalho; M. Y. Kamogawa; L. Martin-Neto (Environmental Chemistry Letters, 2010)

Ecological portrayal of old‐growth forests and persistent woodlands in the Cilento and Vallo di Diano National Park (southern Italy) - M. Marchetti; R. Tognetti; F. Lombardi; U. Chiavetta; G. Palumbo; M. Sellitto; C. Colombo; P. Iovieno; A. Alfani; D. Baldantoni; A. Barbati; B. Ferrari; et al. (Plant Biosystems, 2010)

Double infanticide in a free-ranging group of buffy-headed marmosets, Callithrix flaviceps - Renato R. Hilário; Stephen F. Ferrari (Journal of Ethology, 2010)

The effect of progressive hypoxia on spontaneous activity in single and shoaling golden grey mullet Liza aurata - C. Lefrançois; R. S. Ferrari; J. Moreira da Silva; P. Domenici (Journal of Fish Biology, 2009)
The hypothesis of a differential effect of hypoxia on activity in shoaling v. solitary fish was tested in golden grey mullet Liza aurata . In both solitary and shoaling fish, (1) swimming activity increased significantly at ≤ 60% air saturation compared with normoxia, (2) aquatic surface respiration increased significantly below 15% air saturation and (3) a significant increase in ventilation frequency was observed between 40 and 10% air saturation. Swimming activity was higher in shoaling than in solitary fish, possibly due to social interactions in shoaling fish. Despite showing a higher swimming activity, shoaling individuals showed similar ventilation frequency to the less active solitary fish. This suggests that shoaling exerts a calming effect on L. aurata , probably related to increased safety while in numbers. In addition, shoaling fish spent a higher proportion of time performing aquatic surface respiration at 15% air saturation ( i.e. the highest oxygen level at which aquatic surface respiration was observed) than solitary fish, possibly because of (1) synchronization of aquatic surface respiration in shoaling fish and (2) lower risk of predation perceived by shoaling fish.

Detection of porcine circovirus type 2 (PCV2) from wild boars in central Italy - S. Petrini; S. Barocci; S. Gavaudan; R. Villa; S. Briscolini; M. Sabbatini; C. Mattozzi; F. Barchiesi; S. Salamida; M. Ferrari; M. Paniccià; G. Pezzotti (European Journal of Wildlife Research, 2009)

Molecular genetics of migraine - Boukje de Vries; Rune R. Frants; Michel D. Ferrari; Arn M. J. M. van den Maagdenberg (Human Genetics, 2009)

Initial conditions and their effect on invasion velocity across heterogeneous landscapes - Joseph R. Ferrari; Todd R. Lookingbill (Biological Invasions, 2009)

Productive and metabolic consequences induced by the retained placenta in dairy cows - E. Trevisi; A. R. Ferrari; G. Bertoni (Veterinary Research Communications, 2008)

The effect of acute hypoxia on swimming stamina at optimal swimming speed in flathead grey mullet Mugil cephalus - M. Vagner; C. Lefrançois; R. S. Ferrari; A. Satta; P. Domenici (Marine Biology, 2008)

Meat intake and bladder cancer in a prospective study: a role for heterocyclic aromatic amines? - B. Lumbreras; S. Garte; K. Overvad; A. Tjonneland; F. Clavel-Chapelon; J. P. Linseisen; H. Boeing; A. Trichopoulou; D. Palli; M. Peluso; V. Krogh; R. Tumino; et al. (Cancer Causes & Control, 2008)

Meat intake and bladder cancer in a prospective study: a role for heterocyclic aromatic amines? - B. Lumbreras; S. Garte; K. Overvad; A. Tjonneland; F. Clavel-Chapelon; J. P. Linseisen; H. Boeing; A. Trichopoulou; D. Palli; M. Peluso; V. Krogh; R. Tumino; et al. (Cancer Causes & Control, 2008)

Differential Regulation of the Renin-Angiotensin System by Nicotine in WKY and SHR Glia - Merari F. R. Ferrari; Mohan K. Raizada; Debora R. Fior-Chadi (Journal of Molecular Neuroscience, 2008)

Effects of bilateral adrenalectomy on systemic kainate-induced activation of the nucleus of the solitary tract. Regulation of blood pressure and local neurotransmitters - Merari F. R. Ferrari; Debora R. Fior-Chadi; Gerson Chadi (Journal of Molecular Histology, 2008)

Nicotine Modulates the Renin–Angiotensin System of Cultured Neurons and Glial Cells from Cardiovascular Brain Areas of Wistar Kyoto and Spontaneously Hypertensive Rats - Merari F. R. Ferrari; Mohan K. Raizada; Debora R. Fior-Chadi (Journal of Molecular Neuroscience, 2007)

Adult Stem Cells: Perspectives for Therapeutic Applications - M. Ferrari; A. Corradi; M. Lazzaretti; M. De’Cillà; C. G. Losi; R. Villa; A. Lanfranchi (Veterinary Research Communications, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Do facial gestures, visibility or speed of movement influence gaze following responses in pigtail macaques? - Annika Paukner; James R. Anderson; Leonardo Fogassi; Pier F. Ferrari (Primates, 2007)

Alcohol intake and breast cancer risk: the European Prospective Investigation into Cancer and Nutrition (EPIC) - Anne Tjønneland; Jane Christensen; Anja Olsen; Connie Stripp; Birthe L. Thomsen; Kim Overvad; Petra H. M. Peeters; Carla H. van Gils; H. Bas Bueno-de-Mesquita; Marga C. Ocké; Anne Thiebaut; Agnès Fournier; et al. (Cancer Causes & Control, 2007)

Relationship of alcohol intake and sex steroid concentrations in blood in pre- and post-menopausal women: the European Prospective Investigation into Cancer and Nutrition - S. Rinaldi; P. H. M. Peeters; I. D. Bezemer; L. Dossus; C. Biessy; C. Sacerdote; F. Berrino; S. Panico; D. Palli; R. Tumino; K. T. Khaw; S. Bingham; et al. (Cancer Causes & Control, 2006)

Effect of Weaning and Vaccinations on Immune and Hormonal Parameters in Neonatal Piglets - P. Borghetti; L. Ferrari; V. Cavalli; E. De Angelis; R. Saleri; A. Corradi; P. Martelli (Veterinary Research Communications, 2006)

Cervical muscle response to trunk flexion in whiplash-type lateral impacts - Shrawan Kumar; Robert Ferrari; Yogesh Narayan; Edgar R. Vieira (Experimental Brain Research, 2005)

Blood Compatibility of Cetyl Alcohol/Polysorbate-Based Nanoparticles - J. M. Koziara; J. J. Oh; W. S. Akers; S. P. Ferraris; R. J. Mumper (Pharmaceutical Research, 2005)

Nanometric modulation in apatite - C. Ferraris; T. J. White; J. Plévert; R. Wegner (Physics and Chemistry of Minerals, 2005)

Study on the Virulence, Cell-mediated Immune Response and Histolesivity of Three Field PRRSV Strains with an ORF 5 Genetic Variation - A. Corradi; M. Ferrari; A. M. Cantoni; C. Robotti; L. Alborali; R. Di Lecce; P. Candotti; G. P. Sandri; P. Borghetti (Veterinary Research Communications, 2005)

Vaccination Trials Against Bovine Herpesvirus-1 - G. Castrucci; M. Ferrari; D. Salvatori; S. Sardonini; F. Frigeri; S. Petrini; M. Lo Dico; C. Marchini; A. Rotola; A. Amici; M. Provinciali; A. Tosini; et al. (Veterinary Research Communications, 2005)

Recognition and signalling in the cell wall: The case of endopolygalacturonase, PGIP and oligogalacturonides - B Mattei; R Galletti; C Manfredini; D Pontiggia; G Salvi; S Spadoni; C Caprari; S Ferrari; D Bellincampi; F Cervone; G De Lorenzo (Plant Biosystems, 2005)

Evaluation of Endogenous Pig Retrovirus Expression and of Tumorigenicity in Nude Mice - M. Ferrari; A. Corradi; P.G. Petronini; A. Tosini; A. Toniolo; C. Robotti; R. Moratti (Veterinary Research Communications, 2004)

Segmentation of the fibro-glandular disc in mammogrms using Gaussian mixture modelling - R. J. Ferrari; R. M. Rangayyan; R. A. Borges; A. F. Frère (Medical & Biological Engineering & Computing, 2004)

Identification of the breast boundary in mammograms using active contour models - R. J. Ferrari; A. F. Frère; R. M. Rangayyan; J. E. L. Desautels; R. A. Borges (Medical & Biological Engineering & Computing, 2004)

Dietary P regulates phosphate transporter expression, phosphatase activity, and effluent P partitioning in trout culture - R. M. Coloso; K. King; J. W. Fletcher; P. Weis; A. Werner; R. P. Ferraris (Journal of Comparative Physiology B, 2003)

Tadpoles Assay: Its Application to a Water Toxicity Assessment of a Polluted Urban River - S. O. Demichelis; F. R. de la Torre; L. Ferrari; M. E. García; A. Salibián (Environmental Monitoring and Assessment, 2001)

Long-term in situ Toxicity Bioassays of the Reconquista River (Argentina) Water with Cyprinus carpio as Sentinel Organism - Fernando R. de la Torre; Lucrecia Ferrari; Alfredo Salibián (Water, Air, & Soil Pollution, 2000)

Dietary phosphorus regulates intestinal transport and plasma concentrations of phosphate in rainbow trout - E. M. Avila; H. Tu; S. Basantes; R. P. Ferraris (Journal of Comparative Physiology B, 2000)

Titi monkeys (Callicebus spp., Atelidae: Platyrrhini) in the Brazilian state of Rondônia - Stephen F. Ferrari; Simone Iwanaga; Mariluce R. Messias; Eleildon M. Ramos; Paulo C. S. Ramos; Ernesto H. da Cruz Neto; Paulo E. G. Coutinho (Primates, 2000)

Zoogeography of Chiropotes albinasus (Platyrrhini, Atelidae) in Southwestern Amazonia - Stephen F. Ferrari; Simone Iwanaga; Paulo E. G. Coutinho; Mariluce R. Messias; Ernesto H. Cruz Neto; Eleildon M. Ramos; Paulo C. S. Ramos (International Journal of Primatology, 1999)

Oxidative 4-dechlorination of 2,4,6-trichlorophenol catalyzed by horseradish peroxidase - R. P. Ferrari; Enzo Laurenti; Francesco Trotta (JBIC Journal of Biological Inorganic Chemistry, 1999)

Catechol(amine)s as probes of lactoperoxidase catalytic site structure: spectroscopic and modeling studies - R. P. Ferrari; Silvio Traversa; Luca De Gioia; Piercarlo Fantucci; Gianpaolo Suriano; Elena M. Ghibaudi (JBIC Journal of Biological Inorganic Chemistry, 1999)

MALE HUMPBACK WHALE DIES IN COMPETITIVE GROUP - Adam A. Pack; Dan R. Salden; Mark J. Ferrari; Debbie A. Glockner‐Ferrari; Louis M. Herman; Harrison A. Stubbs; Janice M. Straley (Marine Mammal Science, 1998)

Differential effects of chlordiazepoxide on aggressive behavior in male mice: the influence of social factors - P. F. Ferrari; S. Parmigiani; R. J. Rodgers; P. Palanza (Psychopharmacology, 1997)